1804 Mass. Acts. 111 - (:unkn) unknown (My University, 1805)
Ch. 81, An Act to Provide for the Proof of Fire Arms Manufactured Within this Commonwealth: Requiring appointment of two per county for the inspection of barrels. Barrels required inspection under varying charges of powder and at varying degrees of elevation. Proven barrels are stamped post-inspection. Failed barrels fined thirty cents. Failed pistols fined twenty-five cents. Unproven barrels & pistols fined at ten dollars.
Keywords: MANUFACTURE ONLY